2021
DOI: 10.1111/jace.17619
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oxygen vacancies on piezoelectricity in samarium‐doped Pb(Mg1/3Nb2/3)O3‐PbTiO3 ceramics

Abstract: A study of 0.71Pb(Mg1/3Nb2/3)O3‐0.29PbTiO3 shows that, when it is doped with 2.5% Sm on the A‐site, in addition to an almost threefold increase in piezoelectric charge coefficient and dielectric permittivity, there is a 2 order of magnitude reduction in conductivity, attributed to a decrease in oxygen vacancy concentration. An analysis of the nonlinearity of permittivity with respect to field amplitude shows that both the reversible and irreversible contributions increase significantly with Sm‐doping, with sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The donor-dopant La 3+ in PZT has been intensively studied because it increases the dielectric constant due to relaxor behavior and is suitable for electro-optical applications [137][138][139][140][141]. Sm 3+ has recently drawn attention due to its contribution to a giant electromechanical coupling factor and drastic increase of the piezoelectric coefficient in relaxor-PT systems [142][143][144][145][146][147][148][149][150]. A certain addition of Sm dopant is confirmed to lead to the highest values of d 33 , being on the order of 1500 pC N −1 , and ε T 33 /ε 0 being on the order of 13,000 in PMN-PT ceramic, and d 33 being on the order of 4100 pC N -1 and ε T 33 /ε 0 of ~12,000 in PMN-PT single crystal, respectively [24,146].…”
Section: Soft Piezoelectric Single Crystalsmentioning
confidence: 99%
“…The donor-dopant La 3+ in PZT has been intensively studied because it increases the dielectric constant due to relaxor behavior and is suitable for electro-optical applications [137][138][139][140][141]. Sm 3+ has recently drawn attention due to its contribution to a giant electromechanical coupling factor and drastic increase of the piezoelectric coefficient in relaxor-PT systems [142][143][144][145][146][147][148][149][150]. A certain addition of Sm dopant is confirmed to lead to the highest values of d 33 , being on the order of 1500 pC N −1 , and ε T 33 /ε 0 being on the order of 13,000 in PMN-PT ceramic, and d 33 being on the order of 4100 pC N -1 and ε T 33 /ε 0 of ~12,000 in PMN-PT single crystal, respectively [24,146].…”
Section: Soft Piezoelectric Single Crystalsmentioning
confidence: 99%
“…Li et al. have proved the Sm 3+ substitute Pb 2+ at the A site can reduce the oxygen vacancy concentration, thereby improving the dielectric and ferroelectric properties 11,12,15–19 . On the other hand, Mn‐doped can refine the grains, decrease the leakage current, and improve the remanent polarization 20–24 .…”
Section: Introductionmentioning
confidence: 99%
“…14 Li et al have proved the Sm 3+ substitute Pb 2+ at the A site can reduce the oxygen vacancy concentration, thereby improving the dielectric and ferroelectric properties. 11,12,[15][16][17][18][19] On the other hand, Mn-doped can refine the grains, decrease the leakage current, and improve the remanent polarization. [20][21][22][23][24] Therefore, appropriate addition of Sm 3+ and Mn 2+ can effectively inhibit the formation of oxygen vacancies in PMN-PT films, thereby reducing the leakage current and improving the quality of films.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li et al reported a PMN-PT ceramic with ultrahigh piezoelectric coefficients (d 33 ) of up to 1500 pC/N and dielectric permittivity (ε 33 /ε 0 ) of above 13,000 via the doping of samarium [18]. Due to the unexpectedly high piezoelectric response in Pb-based ferroelectrics, rare earth element doping modification has recently attracted much attention in modifying piezoelectric ceramics [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%